Applied STEM Coursework, High School Dropout Rates, and Students With Learning Disabilities. Issue 5 (July 2018) - Plasman, Jay Stratte; Gottfried, Michael A.
Applied science, technology, engineering, and math (STEM) coursetaking is becoming more commonplace in traditional high school settings to help students reinforce their learning in academic STEM courses. Throughout U.S. educational history, vocational education has been a consistent focus for schools to keep students on the school-to-career pathway. However, very few studies have examined the role of applied STEM coursetaking in improving schooling outcomes for students with learning disabilities. This is a major missing link as students with learning disabilities tend to exhibit much higher dropout rates than students from the general population. This study examines mechanisms displayed through applied STEM courses and the role they play in helping students with learning disabilities complete high school and transition into college. Using a nationally representative data set of high school students and their full transcripts (i.e., Education Longitudinal Study of 2002), we found that students with learning disabilities who took applied STEM courses significantly increased their educational outcomes in the following ways: lowered chances of dropout, increased math test scores, and increased enrollment in postsecondary education. While the general student population also benefited by taking applied STEM courses, the advantages were greater for those students with learning disabilities.